Study of the histomorphology of human pineal gland - Gyanraj Singh; Sudhansu Sekhar Sethi; Sudeepa Das; Chinmayi Mohapatra (Wolters Kluwer Medknow Publications, 2023)
Introduction: Histologically, the pineal gland shows pinealocytes, glial cells, and sometimes calcific concretions. Age-related changes in these three components have been reported by various workers. However, a statistically significant difference between the two sexes has not been found. This study was conducted to find out morphological and histological changes in human pineal gland in relation to advancing age and in relation to gender. Methodology: Forty pineal glands were taken for the study. The pineal glands were fixed in 10% formol saline and processed. Slides for microanatomical study were prepared and observed under microscope. Results: The size of the pinealocytes, size of their nuclei, and number of glial cells increased with age, but it was not significant. The number of pinealocytes decreased with age (P = 0.02). The size of the calcific concretions increased with age (P = 0.02). The difference in size of pinealocytes, nuclei of the pinealocytes, and the number of pinealocytes between genders was not significant. The difference in the number of glial cells between genders was significant (P = 0.03). The difference in the number of concentric lamellated type of calcific concretions between genders was significant (P = 0.03). Conclusion: A histological study of pineal gland in human is an area of interest for anatomists, radiologists, and neurologists. This study has paved a way for us for further research using immunohistochemistry and electron microscopy.